Attitudes of representatives of the contemporary clergy of the Catholic Church towards the phenomenon of suicide in Poland: research report - Chałubińska, Zuzanna (Przegląd Krytyczny, 2025)
Since St. Augustine declared that suicide is the worst sin and an act of defiance against God’s will, there have been debates among Christian leaders about imposing penalties on suicides and their families. The influence of the Church on society has resulted in centuries of stigmatisation of people in suicidal crises. Only the development of psychological sciences brought about changes in thinking, ultimately leading to destigmatisation. In this article, I have summarised my own research conducted on Catholic clergy concerning contemporary attitudes towards suicide and their willingness to provide support to people in suicidal crises. In the last chapter, I present proposals for preventive support involving the Catholic Church, which arose from the clergy’s statements.